Marked asymmetry in vertical force (but not contact times) during running in ACL reconstructed athletes <9 months post-surgery despite meeting functional criteria for return to sport - Thomson, A.; Einarsson, E.; Hansen, C.; Bleakley, C.; Whiteley, R. (Journal of Science and Medicine in Sport, 2018)
Objectives: Compare maximum plantar force (Fmax) during running in soccer players following anterior cruciate ligament reconstruction (ACLR) as they pass return to sport (RTS) criteria. Design: Case control study. Methods: Soccer players after ACLR (n = 16) and matched healthy controls (n = 16) ran on a treadmill at 12, 14 and 16 km/h while plantar loading data was measured using an in-shoe pressure system (Pedar-X, Novel). Fmax and contact time of the injured and uninjured limbs in athletes <9 months post-ACLR and those =9 months ACLR were compared to healthy players (no ACLR). Results: Significant differences with large effect sizes in Fmax asymmetry were seen at all running speeds for the athletes <9 months ACLR compared to those =9 months, and the healthy subjects. Fmax difference peaked at 16 km/h; 32 ± 11%BW in <9 months ACLR group compared to 6 ± 5%BW in =9 months group; ES = 1.67, p < 0.01. There was a non-significant trend for increasing asymmetry with increasing speed for subjects who were <9 months after ACLR while the reverse was true for those =9 months and the healthy subjects. Conclusions: Relatively large unloading of the ACLR limb (but not differences in contact times) are seen during running for athletes <9 months post-ACLR despite having completed functional criteria required to permit RTS training. These asymmetries appear to slightly increase with increasing speed, and the reverse is true for healthy controls and those =9 months after ACLR surgery.